Fuzzy Math, Disclosure Regulation, and Market Outcomes: Evidence from Truth-in-Lending Reform - Stango, Victor; Zinman, Jonathan (Review of Financial Studies, 2011)
We posit that consumer lenders shroud interest rates and market “low monthly payments” to price discriminate on “fuzzy math” or “payment/interest bias”: consumers' pervasive tendency to underestimate borrowing costs when an interest rate is not disclosed. We test whether mandated disclosure changes lenders' ability to price discriminate using within-household interactions between payment/interest bias and policy-induced variation in the strength of Truth-in-Lending Act (TILA) enforcement across lenders and time. Weak TILA enforcement substantially widens the gap between rates paid by more-biased and less-biased borrowers. TILA compliance costs appear to increase interest rates overall, making the net effect on interest rates ambiguous.